Women Friendship in the novel Sula - Bhatta, Saraswati (Journal of Musikot Campus, 2024)
This article examines the historical and cultural experiences of African-American women through the lens of Black feminist thought, with a focus on Toni Morrison’s novel Sula (1973). The research question guiding this study is: How does Sula reflect the complexities of friendship, autonomy, and the quest for empowerment among Black women within a racist and patriarchal society? The study employs a literary analysis method, drawing on the historical context of Black American women’s oppression and the emergence of Black feminist ideology as theorized by scholars like Patricia Hill Collins. Findings reveal that Sula intricately portrays the deep bond between the two protagonists, Sula Peace and Nel Wright, against the backdrop of systemic oppression. Their friendship symbolizes the broader struggle of African-American women to navigate personal autonomy within a community shaped by the legacy of slavery. Sula’s defiance of societal norms, particularly in her relationships with men, highlights the challenges Black women face in seeking empowerment and identity in a society that marginalizes them. This study concludes that Sula not only captures the historical context of Black women’s experiences but also serves as a significant contribution to the discourse on Black feminist thought, emphasizing the importance of friendship, autonomy, and resistance in the fight for liberation.